Modern Methods of Functional Diagnostics in Pediatric Practice - Kholmuradova Zilola Ergashevna; Simran Kumari (Journal of Science in Medicine and Life, 2024)
The study of the functional ability of a particular organ is important when examining both an adult patient and a child. Functional methods allow you to answer a number of questions. Firstly, the results of the study are used to judge how the disease affects the function of an organ or system. Secondly, based on certain parameters, we can judge the compensatory capabilities of the body. Thirdly, by testing with medications or some other influences (physiotherapy, physical activity, etc.), we help the patient select an adequate treatment and regimen. And finally, by conducting dynamic monitoring of the patient with repeated functional examination, the doctor can judge the effectiveness of treatment, carry out timely correction of treatment and rehabilitation measures, and often predict the course of the disease.